Modeling Regional Pollution Transport Events During KORUS‐AQ: Progress and Challenges in Improving Representation of Land‐Atmosphere Feedbacks. Issue 18 (22nd September 2018) - Huang, Min; Crawford, James H.; Diskin, Glenn S.; Santanello, Joseph A.; Kumar, Sujay V.; Pusede, Sally E.; Parrington, Mark; Carmichael, Gregory R.
Abstract: This study evaluates the impact of assimilating soil moisture data from National Aeronautics and Space Administration (NASA)'s Soil Moisture Active Passive (SMAP) on short‐term regional weather and air quality modeling in East Asia during the Korea‐U.S. Air Quality Study (KORUS‐AQ) airborne campaign. SMAP data are assimilated into the Noah land surface model using an ensemble Kalman filter approach in the Land Information System framework, which is semicoupled with the NASA‐Unified Weather Research and Forecasting model with online chemistry (NUWRF‐Chem). With SMAP assimilation included, water vapor and carbon monoxide (CO) transport from northern central China transitional climate zones to South Korea is better represented in NUWRF‐Chem during two studied pollution events. Influenced by different synoptic conditions and emission patterns, impact of SMAP assimilation on modeled CO in South Korea is intense (>30 ppbv) during one event and less significant (<8 ppbv) during the other. SMAP assimilation impact on air quality modeling skill is complicated by other error sources such as the chemical initial and boundary conditions (IC/LBC) and emission inputs of NUWRF‐Chem. Using a satellite‐observation‐constrained chemical IC/LBC instead of a free‐running, coarser‐resolution chemical IC/LBC reduces modeled CO by up to 80 ppbv over South Korea. Consequently, CO performance is improved in the middle‐upper troposphere whereas degraded in the lower troposphere. Remaining negative CO biases result largely from the emissions inputs. The advancements in land surface modeling and chemical IC/LBC presented here are expected to benefit future investigations on constraining emissions using observations, which can in turn enable more accurate assessments of SMAP assimilation and chemical IC/LBC impacts. Key Points: SMAP assimilation most strongly modifies short‐term regional atmospheric modeling skill in East Asia transitional climate zones SMAP assimilation improves water vapor and carbon monoxide transport from northern central China to South Korea SMAP assimilation impact on air quality modeling skill in part relies on the quality of model chemical IC/LBC and various emission inputs